Research challenges models of service processes in networks without queues - Пономаренко, Л. А.; Паладюк, В. В. (Problems of Informatization and Control, 2008)
The model process service calls in wireless communication networks with different access strategies. The models that use the most famous CAC (Call Admission Control - access control calls), based on GC-circuit (Guard Channels - watch channels, the channels are reserved only for the h-Call) access to public kansypv base station cell. Then explore the isolated cell model in which access control strategy adopted diverse challenges channels basic cell selection based on individual h-channels for calls. It is also the generalization of this strategy access channels